Neurons generated from APP/APLP1/APLP2 triple knockout embryonic stem cells behave normally in vitro and in vivo: lack of evidence for a cell autonomous role of the amyloid precursor protein in neuronal differentiation - Bergmans, Bruno A.; Shariati, Ali; Habets, Ron L.P.; Verstreken, Patrik; Schoonjans, Luc; Müller, Ulrike C.; Dotti, Carlos G.; De Strooper, Bart (Stem cells, 2010)
Alzheimer's disease amyloid precursor protein (APP) has been implicated in many neurobiologic processes, but supporting evidence remains indirect. Studies are confounded by the existence of two partially redundant APP homologues, APLP1 and APLP2. APP/APLP1/APLP2 triple knockout (APP tKO) mice display cobblestone lissencephaly and are perinatally lethal. To circumvent this problem, we generated APP triple knockout embryonic stem (ES) cells and differentiated these to APP triple knockout neurons in vitro and in vivo. In comparison with wild-type (WT) ES cell-derived neurons, APP tKO neurons formed equally pure neuronal cultures, had unaltered in vitro migratory capacities, had a similar acquisition of polarity, and were capable of extending long neurites and forming active excitatory synapses. These data were confirmed in vivo in chimeric mice with APP tKO neurons expressing the enhanced green fluorescent protein (eGFP) present in a WT background brain. The results suggest that the loss of the APP family of proteins has no major effect on these critical neuronal processes and that the apparent multitude of functions in which APP has been implicated might be characterized by molecular redundancy. Our stem cell culture provides an excellent tool to circumvent the problem of lack of viability of APP/APLP triple knockout mice and will help to explore the function of this intriguing protein further in vitro and in vivo. STEM CELLS 2010;28:399-406
Gesehen am 20.01.2023